1385 Berotralstat prophylaxis for Hereditary Angioedema – an audit of use in a cohort of patients at a tertiary centre. (17th August 2022) - Dzora, Ella; O'Sullivan, Catherine; Buckland, Matthew
Abstract : Aims: Hereditary Angioedema is a rare disorder, affecting 1:10-50, 000. In 2021 the National Institute for Health and Care Excellence (NICE) published guidance on the use of Berotralstat for preventing recurrent attacks of hereditary angioedema (HAE) 1 in children 12 years and older. Berotralstat is an oral plasma kallikrein inhibitor which has the end result of inhibiting bradykinin and therefore reducing vasodilation, vascular permeability and ultimately reducing oedema and pain in HAE. Prior to the new recommendations children with recurrent attacks of angioedema would have had limited treatment options. Although attenuated androgens are licenced for use they may not be a practicable solution due to lack of availability, intravenous access or needlephobia, or concerns about appropriate use due to pubertal status. As Berotralstat is currently a new and unique treatment, we wanted to audit our single centre experience in a cohort of children with hereditary angioedema, some of whom have had access through early access schemes ahead of this guidance. Methods: We audited the 27 patients that the team manages who have hereditary angioedema (HAE). We focused on the age ranges, age of onset of symptoms, current prophylaxis, number of symptomatic episodes, emergency care plan and access to emergency therapy. Results: Our cohort included four patients who are being managed on Berotralstat, all over the age of 12 years. Three of these patients had non C1 HAE, with one having a mutation in the FXII gene (HAE-FXII). The rest of the patients were on prophylaxis as shown in table 1 . Treatment that was stopped in favour of Berotralstat included: Patient 1) No active prophylaxis – Failed Tranexamic Acid Patient 2) Tranexamic acid Patient 3) Tranexamic acid Patient 4) Desogestrel and Tranexamic acid prior use of Lanadelumab All patients on long term prophylaxis (Tranexamic Acid, Berotralstat or Lanadelumab) had a meaningful reduction in attack frequency. Conclusion: Although there are small numbers of patients on Berotralstat we have found that it has reduced attack frequency and severity in all patients. It also reduces the overall medication burden of patients, both in number of different medications and the need for intravenous or subcutaneous injections for breakthrough attacks and we have not had any treatment discontinuations due to adverse events. In response to this audit we developed a form that could be edited and stored on the electronic notes system that would be completed for each patient with HAE, which offers a scoring assessment of the burden of HAE on the lives of patients and carers. We have also developed an electronic care plan that improves information sharing about prophylaxis and rescue treatment for acute attacks. Reference: National Institute for Health and Care Excellence (2021) Berotralstat for preventing recurrent attacks of hereditary angioedema (TA738) NICE.